Communicating social and environmental issues effectively - Reed, Betsy (PRCA practice guides., 2020)
As awareness of social and environmental issues becomes more central to business and reputational success, communications and marketing professionals need to be able to make the most of opportunities to communicate effectively about these issues. This is the definitive guide to planning and delivering great communications on complex social and environmental issues. Outlining the steps needed to plan, risk-proof and execute effective communications strategies, the book provides a clear framework to help leaders, communications managers and marketing practitioners build the knowledge and skills needed to spot risks and opportunities around complex issues, such as climate change and ethical supply chains. Including real-world case studies, practical exercises and further reading, each chapter offers a beginning-to-end framework: from making the business case and mapping stakeholders, to messaging, framing relevant tactics, and then risk-assessing the plan. Whether a local authority, brand, educational institution or senior leader, this guide will equip you with all the necessary skills to make your communications effective.